Home » Let f(x) = 2x + 4 and g(x) = 6x + 7 here g(x) >…

Let f(x) = 2x + 4 and g(x) = 6x + 7 here g(x) >…

Let f(x) = 2x + 4 and g(x) = 6x + 7 here g(x) > 0. Solve the inequality (frac{f(x)}{g(x)})

  • A.
    x
  • B.
    x > – (frac{4}{3})
  • C.
    x > – (frac{3}{4})
  • D.
    x > – 12
Correct Answer: Option C
Explanation

(frac{f(x)}{g(x)})

∴ (frac{2x +4}{6x + 7})

= 2x + 4

= 6x + 7 > 2x + 4
= 6x – 2x > 4 – 7
= 4x > -3
∴ x > -(frac{3}{4})

Related:  The base diameter of a cone is 14cm, and its volume is 462 cm3. Find...